2021
DOI: 10.1101/2021.08.23.457327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential gene expression reveals host factors for viral shedding variation in mallards (Anas platyrhynchos) infected with low-pathogenic avian influenza virus

Abstract: Intraspecific variation in pathogen shedding impacts disease transmission dynamics; therefore, understanding the host factors associated with individual variation in pathogen shedding is key to controlling and preventing outbreaks. In this study, ileum and bursa of Fabricius tissues of mallards ( Anas platyrhynchos ) infected with low-pathogenic avian influenza (LPAIV) were evaluated at various post-infection time points to determine genetic host factors associated with intraspecific variation in viral shedd… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 184 publications
(152 reference statements)
1
8
0
Order By: Relevance
“…In the bursa, we did not observe any DETs in group I1 or group I2 [1]. While no DEGs were observed between shed level groups in the bursa of group I1, 17 DEGs were observed in group I2 (), 88 % of which had expression levels higher in high shedders compared to low/moderate shedders, a pattern consistent with DEGs in the ileum.…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…In the bursa, we did not observe any DETs in group I1 or group I2 [1]. While no DEGs were observed between shed level groups in the bursa of group I1, 17 DEGs were observed in group I2 (), 88 % of which had expression levels higher in high shedders compared to low/moderate shedders, a pattern consistent with DEGs in the ileum.…”
Section: Resultssupporting
confidence: 64%
“…Differential gene expression was not observed between LPAIV-infected and uninfected control birds at each DPI in the bursa or ileum [1], despite our lenient DEG screening criteria. In previous studies, differential gene expression was observed between AIV-infected and uninfected poultry [29, 42–44, 97]; yet, in studies that looked at both LPAIV and highly pathogenic AIV (HPAIV), gene expression was up-regulated at higher levels in HPAIV-infected birds compared to LPAIV-infected birds [42–44].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations